The Role of PPARs in the Endothelium: Implications for Cancer Therapy - David Bishop-Bailey; Karen E. Swales (PPAR Research)
The growth and metastasis of cancers intimately involve the vasculature and in particular the endothelial cell layer. Tumours require new blood vessel formation via angiogenesis to support growth. In addition, inflammation, coagulation, and platelet activation are common signals in the growth and metastasis of tumour cells. The endothelium plays a central role in the homeostatic control of inflammatory cell recruitment, regulating platelet activation and coagulation pathways. PPAR𝛼, -𝛽/𝛿, and -𝛾 are all expressed in endothelial cells. This review will discuss the roles of PPARs in endothelial cells in relation to angiogenesis, inflammation, coagulation, and platelet control pathways. In particular, we will discuss the recent evidence that supports the hypothesis that PPAR𝛼 and PPAR𝛾 are antiangiogenic receptors, while PPAR𝛽/𝛿 is proangiogenic.